Pemertahanan Bahasa Ocu pada Interaksi Masyarakat di Kawasan Wisata Sungai Gelombang Kampar Riau (Kajian Sosiolinguistik) - Ahmad Zikri; Afi Fadlillah (Logat: Jurnal Bahasa Indonesia dan Pembelajaran, 2022)
This study focuses on the preservation of the regional language (Ocu language) in the Kampar community interactions that occur in the Sungai Gelombang tourist area. This language preservation research was carried out so that the position of the Ocu language could be upheld by the Kampar people and to document the language so that it would not experience a shift or extinction. This research uses sociolinguistic and qualitative research methods. While the research technique used is observation (observation). The results of this study indicate language retention in the form of four patterns, namely: (1) buyer and seller relationship patterns, (2) seller and buyer relationship patterns, (3) visitor relationships with visitors, and (4) parking guard relationships with visitors. Then, the factors that cause the maintenance of the Ocu language in community interactions in the Sungai Gelombang are cultural, educational, economic, and social factors.